Targeting T helper 17 cells: emerging strategies for overcoming transplant rejection - Young Joon Lee; Mi-La Cho (Clinical Transplantation and Research)
Solid organ transplantation has significantly improved the survival rate of patients with terminal organ failure. However, its success is often compromised by allograft rejection, a process in which T helper 17 (Th17) cells play a crucial role. These cells facilitate rejection by enhancing neutrophil infiltration into the graft and by activating endothelial cells and fibroblasts. Additionally, Th17 cells can trigger the activation of other T cell types, including Th1, Th2, and CD8+ T cells, further contributing to rejection. An imbalance between Th17 and regulatory T cells (Tregs) is known to promote rejection. To counteract this, immunosuppressive drugs have been developed to inhibit T cell activity and foster transplant tolerance. Another approach involves the adoptive transfer of regulatory cells, such as Tregs and myeloid-derived suppressor cells, to dampen T cell functions. This review primarily focuses on the roles of Th17 cells in rejection and their interactions with other T cell subsets. We also explore various strategies aimed at suppressing T cells to induce tolerance.